2023
DOI: 10.1097/sla.0000000000005867
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Strategies Intended to Prevent Surgical Site Infection After Lower Limb Revascularization Surgery

Abstract: Objective: The objective of this study is to evaluate the efficacy of strategies intended to prevent surgical site infection (SSI) after lower limb revascularization surgery. Background: SSIs are common, costly complications of lower limb revascularization surgery associated with significant morbidity and mortality. Methods: We searched MEDLINE, EMBASE, CENTRAL, and Evidence-Based Medicine Reviews (inception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…In previous studies, insufficient randomised controlled trial evidence was found to evaluate the advantages and disadvantages of surgical antibiotic prophylaxis for SSI prevention 20 , 21 . However, the effect of surgical antibiotic prophylaxis on SSI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, insufficient randomised controlled trial evidence was found to evaluate the advantages and disadvantages of surgical antibiotic prophylaxis for SSI prevention 20 , 21 . However, the effect of surgical antibiotic prophylaxis on SSI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This animal study showed that their specific antibiotic composition with minocycline and rifampin with chlorhexidine precoating resisted to Staphylococcus aureus and limited the growth of Pseudomonas aeruginosa . However, clinical experience is heterogenous and diverse surveys show mixed opinions about preventive usage of antibiotic-bonded grafts [ 31 , 32 ]. Furthermore, S. aureus has been shown to colonize rifampin-bonded grafts 7 days after implantation [ 33 ].…”
Section: Preventionmentioning
confidence: 99%